Reaction Based Approach to find Malicious Posts in Online Social Networks - khan, Rubina; khurana, Anshul (International Journal of Computer Sciences and Engineering, 2025)
Social network is a platform of connected peoples where peoples share relation, emotions, activities etc. Second generation social network come in existence with lots of emerging applications, which also support service oriented environment, during all kind of activities massive information is generated. These all information are in the form of post. Hence it is necessary to find category of post. A post may be legitimate or malicious. In this dissertation we are trying to find malicious post on the basis of reaction and share on particular post. All the post collected by facebook through app known as Netvizz. Entire concept implemented in R studio which is an IDE of R programming. Dissertation also contain statistical analysis of page network with the help of well known tool gephi, It is based on predefine parameter such as Eigen vector centrality,closeness ,betweenness etc